Kecerdasan Emosional, Perilaku Belajar, Kompetensi Dosen dan Tingkat Pemahaman Akuntansi - Lameng, Alexandro Aditya Dewa Bharata; Damayanthi, I Gst Ayu Eka (E-Jurnal Akuntansi, 2022)
The purpose of the study was to obtain empirical evidence regarding the influence of emotional intelligence, learning behavior, and lecturer competence on the level of accounting understanding. The study involved students majoring in accounting for the 2016-2017 undergraduate program, Faculty of Economics and Business, Udayana University. The number of samples taken as many as 117 student respondents using purposive sampling method. Data was collected by means of a questionnaire. The analysis technique used is multiple linear regression analysis technique. The results of this study indicate that learning behavior and lecturer competence have a positive and significant effect on the level of accounting understanding. While emotional intelligence has no effect on the level of understanding of accounting. Keywords: Emotional Intelligence; Learning Behavior; Lecturer Competence; Accounting Understanding Level.